ANALISIS PERBUATAN BERLANJUT PADA PUTUSAN NOMOR 2121/PID.SUS/2022/PN TNG DALAM TINDAK PIDANA PENCABULAN ANAK: The Analysis of The Action Was Continued In Decision Number 2121/Pid.Sus/2022/PN Tng In The Crime of Child Molestation - Destha Oeilasthi Hanyakrawati Paramartha; Rini Purwaningsih (Faculty of Law, Universitas Trisakti, 2025)
In this crime of child molestation, the application of criminal sanctions that have been regulated is often imposewd more lightly and the maximum that is threatened in the law is regulated in law Number 35 of 2014 concerning child protection. The author identification the problem about how was the criminal act of abuse committed by the perpetrator in decision number 2121/Pid.Sus/2022/PN Tng? And is the crime of continuous abuse as stated in decision number 2121/Pid.Sus/2022/PN Tng an aggravating factor? Normative research using secondary data, data collection hrough literature studies, qualitative analysis, and conclusions using deductive methods. The research and conclusion of this study is that there has been a continuous crime of child molestation. The author hopes that the results of this study can contribute to the development of criminal law and child molestation in Indonesia.